Os programas de qualificação e a ideologia da empregabilidade sob a égide do neoliberalismo: a experiência do Brasil a partir dos anos 90 - PINHO, Marcelo Ricarte (2018)
The present study aims to discuss the scope and limits of professional qualification programs, from the year 1990, as an alternative to cope with unemployment. It promotes the theoretical debate about the phenomenon of unemployment and changes that have occurred in the world of work resulting from the process of capitalist restructuring. It deals with the replacement of the concept of qualification by the concept of competence and the theoretical principles on which are based the PLANFOR, the PNQ and PRONATEC as prime examples of their times of application of the concept of employability, its coherence and adequacy, faced with the reality that proposed to modify. The limits of the programs of qualification are verified through the analysis of official reports from the government on the reintegration of workers into the labor market, with a focus on the results achieved by the workers of Maranhão, in terms of change in their condition of unemployment. It is concluded that the professional qualification programs not allowed to workers of Maranhão face unemployment.